Breaking Through the Blister : Exploring Chronic Bullous Disease of Chidhood - Revinanda Venincia Pangaribuan; Cut Putri Hazlianda (Talenta Publisher, 2025)
Background : One of the autoimmune disease occurs on the first decade of life is Linear Immunoglobulin A Bullous Disease that initially referred to as Chronic Bullous Disease of Childhood is an infrequent and nonhereditary skin disorder defined by a linear accumulation of immunoglobulin A. The lesions present as clear or hemorrhagic vesicles (or both) or bullae that emerge from otherwise normal skin, occasionally accompanied by an erythematous or urticarial base. The bullae or vesicles are typically tense, vary in size, and often develop into annular or polycyclic plaques as a result of the lesions merging together. CBDC is a self-limiting disease, with most children experiencing recovery within two years of the symptom beginning, in some cases, the disease continues into puberty, but it is typically less severe than the initial eruption. Objective : This literature review aims to provide a comprehensive understanding of CBDC, including its pathogenesis, diagnosis and appropriate therapeutic approaches for managing the disease. Methods : Herein, using the key terms: â€œChronic Bullous Disease of Chidhoodâ€, â€œLinear Immunoglobulin A Bullous Diseaseâ€, â€œautoimmune bullous diseaseâ€, we carried out a review of the literature, using Google Scholar, PubMed and book in last 10 years. Conclusion : CBDC is a chronic bullous disease that appears in pediatric age. The pathogenesis of this disease is not yet known with certainty. Although the disease is capable of self-healing, dapsone is the recommended first-line treatment. If spontaneous recovery takes place, the prognosis is often optimistic. Accurate diagnosis and therapy are important for a prognosis. Latar belakang : Salah satu penyakit autoimun bulosa yang muncul pada decade pertama kehidupan adalah Penyakit Linear Immunoglobulin A yang awalnya disebut Chronic Bullous Disease of Childhood, merupakan kelainan kulit yang jarang terjadi dan tidak bersifat keturunan ditandai dengan akumulasi linear IgA. Lesi muncul sebagai vesikel bening atau hemoragik (atau keduanya) atau bula yang muncul dari kulit normal, kadang-kadang disertai dengan dasar eritematosa atau urtikaria. Bula atau vesikel biasanya tegang, ukurannya bervariasi, dan sering berkembang menjadi plak anular atau polisiklik akibat bergabungnya lesi. CBDC merupakan penyakit yang dapat sembuh dengan sendirinya, dengan sebagian besar anak mengalami pemulihan dalam waktu dua tahun sejak gejala muncul, dalam beberapa kasus, penyakit ini berlanjut hingga masa pubertas, namun biasanya tidak separah gejala awal. Tujuan : Tinjauan pustaka ini bertujuan untuk memberikan pemahaman yang komprehensif tentang CBDC, termasuk patogenesis, diagnosis dan pendekatan terapi yang tepat untuk penyakit ini. Metode : Dalam penelitian ini, menggunakan istilah kunci: “Penyakit Bulosa Kronis pada Anak”, “Penyakit Bulosa Imunoglobulin A Linear”, “penyakit bulosa autoimun”, kami melakukan telaah pustaka, menggunakan Google Scholar, PubMed dan buku dalam 10 tahun terakhir. Kesimpulan: CBDC merupakan penyakit bulosa kronis yang muncul pada usia anak-anak. Patogenesis penyakit ini belum diketahui secara pasti. Meskipun penyakit ini mampu sembuh sendiri, dapson merupakan pengobatan lini pertama yang direkomendasikan. Jika terjadi pemulihan spontan, prognosisnya sering kali optimis. Diagnosis dan terapi yang akurat penting untuk prognosis.